Application and Impact of HR Analytics on Talent Management, Branding and Challenges - Sriram Prabhakar; S Jayaprakash (Business, Management and Economics: Research Progress Vol. 2, 2024)
Background and Purpose: HR departments play an important role in aligning the performance of each employee with the goals and objectives of the organization. Making wiser decisions about employees to improve performance at the individual and/or organizational levels is the process of HR analytics. HR analytics is a method for determining the correlation between HR practices and organizational performance outcomes such as sales volume or customer satisfaction. Human Resource Analytics was established in 1978 by Jac Fitz-Enz, the pioneer of human capital strategic analysis and performance benchmarking. In this paper, the researcher discusses the concept of HR analytics, its application, its impact on talent management, branding, and challenges in its application. Methodology: The researcher examines secondary data and conducts a thorough literature review to understand the concept and its application across industries and nations, as well as to identify any challenges encountered during deployment and any benefits perceived by various industry professionals. Findings: The findings of the study indicate that the use of HR analytics may be of assistance to businesses in the process of creating their brand and acquiring a competitive edge in the present business environment, which is defined by strong competition. Furthermore, it has the potential to enhance the productivity of the workforce as well as the output of the personnel. Conclusion: By enhancing HR rules and processes, HR analytics may undoubtedly increase the department’s reputation. To effectively cooperate on HR analytics initiatives, HR professionals are gaining new skills and competencies. HR professionals must become proficient at demonstrating the effects of HR strategies on business outcomes. Conducting exploratory research on the problems and obstacles to HR analytics adoption in enterprises can be part of the future scope.